Perkawinan Dini: Menyingkap Dampaknya Terhadap Kesehatan Anak di Kota Bandar Lampung - Ahmad, Nur Qalbi Putri Ramadhani; Wati, Dwi Shinta; Aldika, Muhammad Ardan; Satria, Indah (Jurnal Litigasi Amsir, 2024)
This paper aims to identify the impact of adolescent health on child marriage. In addition, it provides policy recommendations related to reproductive and sexual health for adolescents. This article is based on research using normative and empirical juridical methods through focus group discussions and in-depth interviews in Bandar Lampung City 2023 and comes from library data. Focus group discussions were conducted with judges at the Tanjung Karang Religious Court Class 1A to obtain information regarding the health impacts experienced by teenagers who engage in child marriage. This research succeeded in identifying the health impact. The dominant factor why child marriage occurs is the lack of comprehensive reproductive and sexual health education (PKRS) from an early age to provide teenagers with a proper understanding of their choices. Therefore, providing extensive knowledge of reproductive health from an early age in schools and reviewing Law No. 1 of 1974 in conjunction with Law No. 16 of 2019 concerning marriage is recommended.